Legal Analysis of Health Professional Ethics in Improving Health Services in the Perspective of Islamic Law - Widya Sabila; Irwansyah Irwansyah; Afri Ningtias; Ahmad Zaki (PROMOTOR, 2024)
Health is a human right and one of the elements of welfare that must be realized in accordance with the ideals of the nation as stated in Pancasila and the 1945 Constitution of the Republic of Indonesia. Regarding the matters already listed in the 1945 Constitution, health workers in serving the community, are also bound by ethics and health law. In carrying out health services, health workers must comply with professional ethics (professional code of ethics) and also comply with the law, the rules set out in the law. Ethics in medical action in Islamic literature is known as adab. Adab in hadith and early post-Islamic literature means proper speech, good ethics, and correct procedures. Islamic law has laid down rules that concern health services and care, including the health of society and the state at large and has contributed greatly to the modern medical science that is developing today. With this research, the researcher conducts research activities objectively on the reality of the subject under study, in the sense that reality is seen from the angle of those being studied. This qualitative research is more concerned with the accuracy and adequacy of the data.